INVESTIGATION OF MICRO BUBBLE FOR THE REMOVAL OF SUSPENDED PARTICLE AND ENHANCEMENT OF DISSOLVED OXYGEN IN POLLUTED WATER - WISMO WINARTO, FELIXTIANUS EKO (2012)
Filtration and precipitation are generally used in wastewater treatment to separate pollutants. However, they are not cost effective and have problems of filter waste and time consumption. The smaller particles are left even after a filtration process, depending upon the porosity of the filter. This research proposes a new approach of using compressed air to lift up micro suspended particles in polluted water. The novelty of the approach is in its sustainability, cost effectiveness and faster solution to micro pollutant separation. Air is forced through a submerged micro diffuser to produce micro bubbles, which flow upward and entrain suspended particles to separate them from water. The study was carried experimentally and a lab test rig was designed and implemented. Bubble size plays an important role in moving suspended particles upwards due to the buoyancy force, which in turn depends upon the vertical component of bubble velocity. Generally, the larger bubbles tend to change shape due to high buoyancy force. The bubble velocity is characterized by the Froude number and Reynolds number. The strategies to control the bubble size in monodispersed (single size) and polydispersed (multi size) cases are presented in this research. To simulate the real wastewater physiochemical characteristics (surface tension, density, viscosity, etc), Glycerin is added to distilled water in various volume fractions of 0.1% to 0.5%. The relationship between air pressure, vertical and horizontal velocities, as well as bubble size is studied. These parameters (bubble diameter, vertical velocity) lead to high effectiveness of suspended particles separation, and are validated by measuring the low concentration of pollutant (PPM), corresponding to the turbidity level. The amount of suspended particles in relation to turbidity has been studied and it is found that the turbidity level of 6.9 NTU decreases to 3.66 NTU, using 1-10 micron porous sintered glass as a submerged diffuser and at 12 10-3 m3/min air flow. In most biological wastewater treatment systems, a submerged diffuser is used to provide oxygen and mixing to degrade the organic matter. In this study, the effectiveness of micro diffusers in the degradation of organic matter was investigated. The nitrification performance using both micro and macro diffusers was evaluated by measuring ammonium-nitrogen (NH4-N) and nitrate-nitrogen (NO3-N). The experimental values were compared with the theoretical values derived from the kinetic calculations. Two batch experiments were conducted for the estimation of the kinetic parameters for the degradation and the nitrification of organic matter at 1 hour, 3 hours, 6 hours, and 24 hours until 48 hours, in steps of 3 hours for each batch of experiments. From the measurement results, the degradation kinetic COD parameter (kCOD) of the micro diffuser was found to be 1.46 times higher than the macro diffuser. Therefore the degradation kinetics of soluble COD parameter (ksCOD) of the micro diffuser was found to be 1.5 times higher than macro diffuser. The difference between micro and millimeter diffusers in removed COD was approximately 6%. , and in removed sCOD was approximately 16%. The main data parameters in Nitrification of wastewater were ammonium and nitrate. The measurement results of ammonium and nitrate using micro diffuser was achieved at 3% higher than macro diffuser.